Smoking Status and Cognitive Function in a National Sample of Older Adults - Zhang, Qiaoyang; Zhang, Min; Chen, Yun; Zhu, Shumin; Zhou, Wang; Zhang, Lihao; Dong, Guanzhong; Cao, Yin (Frontiers in Psychiatry, 2022)
Abstract Aims: To examine the correlation between smoking status and different domains of cognitive function in elderly Americans. Methods: We used data from the 2011 to 2014 U.S. National Health and Nutrition Examination Survey (NHANES). Participants over 60 years with available smoking history and cognitive function data were enrolled in our analysis. The NHANES study included the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) assessment, the Animal Fluency Test (AFT), and the Digit Symbol Substitution Test (DSST) to assess cognition. Multivariate regression analyses were used to estimate the association between cigarette smoking and cognitive function. Results: A total of 2,932 participants were enrolled in the analysis, including 372 (12.7%) current smokers, 1,115 (38%) former smokers, and 1,445 (49.3%) never smokers. Never smokers had in average 3.82 (95% CI, 2.21 to 5.43) points more than current smokers in the DSST, whereas former smokers had 3.12 (95% CI, 1.51 to 4.73) points more than current smokers. Besides, smoking was not associated with the results of the AFT or the CERAD test. Conclusions: This study suggests that cigarette smoking is associated with processing speed among the American elderly.